Spatial distribution of superconducting and charge-density-wave order parameters in cuprates and its influence on the quasiparticle tunnel current (Review Article) - Gabovich, Alexander M.; Voitenko, Alexander I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The state of the art concerning tunnel measurements of energy gaps in cuprate oxides has been analyzed. A detailed review of the relevant literature is made, and original results calculated for the quasiparticle tunnel current J(V) between a metallic tip and a disordered d-wave superconductor partially gapped by charge density waves (CDWs) are reported, because it is this model of high-temperature superconductors that becomes popular owing to recent experiments in which CDWs were observed directly. The current was calculated suggesting the scatter of both the superconducting and CDW order parameters due to the samples’ intrinsic inhomogeneity. It was shown that peculiarities in the current-voltage characteristics inherent to the case of homogeneous super-conducting material are severely smeared, and the CDW-related features transform into experimentally observed peak-dip-hump structures. Theoretical results were used to fit data measured for YBa2Cu3O7–δ and Bi2Sr2CaCu2O8+δ. The fitting demonstrated a good qualitative agreement between the experiment and model calculations. The analysis of the energy gaps in high-Tc superconductors is important both per se and as a tool to uncover the nature of superconductivity in cuprates not elucidated so far despite of much theoretical effort and experimental progress.